Blood pressure and cardiovascular risk factors in women treated for climacteric symptoms with acupuncture, phytoestrogens, or hormones. Issue 9 (September 2020) - Palma, Federica; Fontanesi, Francesca; Neri, Isabella; Xholli, Anjeza; Facchinetti, Fabio; Cagnacci, Angelo
Abstract: Objective: To evaluate the response of cardiovascular risk factors to the treatment of climacteric symptoms. Methods: In this prospective study, women reporting climacteric symptoms were randomized to 3 months of treatment with either acupuncture ( n  = 19), phytoestrogens (75 mg soy isoflavones, BID; n  = 22), or low-dose hormone therapy (HT; 0.3 mg conjugated equine oestrogens plus 1.5 mg medroxyprogesterone acetate; n  = 20). Greene's climacteric scale, blood pressure (BP), lipids, glucose, insulin, and homeostatic model assessment of insulin resistance were assessed before and after treatment. Observed changes were compared by analysis of variance. Results: HT and acupuncture reduced Greene climacteric score to a similar extent, but the effect of phytoestrogens was significantly lower ( P  < 0.05). With acupuncture, systolic (−7.4 ± 15.3 mm Hg; P  < 0.05) and diastolic BP (−8.3 ± 7.7mm Hg; P  < 0.01) decreased, and the same occurred with phytoestrogens (−8.4 ± 9.0 mm Hg [ P  < 0.01] and −6.6 ± 7.9 mm Hg [ P  < 0.01]). Neither BP systolic (1.9 ± 17.5 mm Hg) nor BP diastolic (−1.4 ± 9.6 mm Hg) changed during HT. Low-density lipoprotein cholesterol decreased with phytoestrogens (−9.9 ± 19.6 mg/dL; P  < 0.05), and triglycerides increased with both HT (34.5 ± 12.2 mg/dL; P  < 0.01) and phytoestrogens (17.41 ± 24.4 mg/dL; P  < 0.01). A slight but significant increase in homeostatic model assessment of insulin resistance (0.14 ± 0.5; P  < 0.05) was observed after HT. Conclusions: Treatment of climacteric symptoms with acupuncture and phytoestrogens, but not HT, is associated with a clear BP reduction, and phytoestrogens with potentially positive alterations in low-density lipoprotein cholesterol level. Trial Registration: EudractCT Number 2008-006053-41. N/A: Video Summary: http://links.lww.com/MENO/A637 . Abstract : Supplemental Digital Content is available in the text